Role of College Environment on Students' Soft Skills: Achievement Goal Structure. Issue 4 (2nd October 2022) - Zhang, Qiannan; Lin, Sheng; Liu, Jinlan; Zhang, Jingyi
Abstract: The development of undergraduate students' soft skills is crucial because their chances to satisfactorily deal with the demands of various environments and interlocutors increases with the development of their soft skills. Based on the achievement goal theory, this study aimed to examine the role of the school environment in fostering students' soft skills. Structural equation modeling was conducted to examine the relationships between five environmental factors—learning task, teacher support, extracurricular activities, interaction with teachers and peers, and soft skills. These findings positively predicted soft skills in college environments with development and competence growth, for both in-class and out-of-class contexts. In addition, the findings revealed that the most effective methods to facilitate students' soft skills development included supporting extracurricular activities, engaging students in high-order learning tasks, facilitating peer learning, and providing structured guidance.